2008
DOI: 10.1007/s11695-008-9453-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Morbid Obesity and Insulin Resistance on Gene Expression Levels of AQP7 in Visceral Adipose Tissue and AQP9 in Liver

Abstract: The tendency toward an elevation of mRNA expression of VAT AQP7 in obesity together with the decreased hepatic AQP9 expression observed in obese T2DM subjects suggests a potential role in facilitating glycerol release from adipose tissue and reducing glycerol entry into hepatocytes in obesity and T2DM, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 36 publications
3
58
1
3
Order By: Relevance
“…The decrease in AQP7 might reflect an overall decreased lipolytic capacity, thereby promoting the maintenance of lipid stores and a progressive adipocyte hypertrophy. 52,53 On the other hand, de novo synthesis of the FFA or lipogenesis produced in adipocytes further contributes to fat accumulation. SREBP1 (originally named ADD1, adipocyte determination and differentiation dependent factor 1) is a transcription factor that regulates the expression of lipogenic genes.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in AQP7 might reflect an overall decreased lipolytic capacity, thereby promoting the maintenance of lipid stores and a progressive adipocyte hypertrophy. 52,53 On the other hand, de novo synthesis of the FFA or lipogenesis produced in adipocytes further contributes to fat accumulation. SREBP1 (originally named ADD1, adipocyte determination and differentiation dependent factor 1) is a transcription factor that regulates the expression of lipogenic genes.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies evaluating the AQP7 mRNA expression in association with T2D did not find significant changes in the expression in SAT or VAT (Ceperuelo-Mallafre et al , Catalan et al 2008, Miranda et al 2009, Lebeck et al 2012a, but an increased AQP7 abundance in VAT (Miranda et al 2010, Rodriguez et al 2011 has also been reported. These studies were performed in mixed gender cohorts, except for two studies (Catalan et al 2008, Lebeck et al 2012a.…”
Section: Figurementioning
confidence: 99%
“…The relative expression of AQP9 in the liver has been investigated in obese individuals with T2D and obese with no impairment of their glucose tolerance. This has given variable results with some reporting a reduced expression of AQP9 in T2D (Catalan et al 2008, Rodriguez et al 2011 and others finding no significant changes (Miranda et al 2009). These findings contrast the increased expression of AQP9 found in male rodent models of diabetes , Carbrey et al 2003.…”
Section: Human Studies On Aqp9 Expressed In Livermentioning
confidence: 99%
“…In humans, AQP7 expression levels were found to be significantly decreased in severely obese women compared with lean and nonseverely obese subjects [24]. However, other investigators have reported a different result, namely that AQP7 transcript levels tended to be increased in women with nonsevere obesity compared with lean women [25]. In terms of the PCOS, our present study showed that AQP7 expression, at both the mRNA and protein levels, is significantly higher in PCOS individuals (p < 0.05) compared to controls.…”
Section: Discussionmentioning
confidence: 99%